A simple spiro-type hole transporting material for efficient perovskite solar cells1. Issue 7 (1st July 2015) - Ganesan, Paramaguru; Fu, Kunwu; Gao, Peng; Raabe, Ines; Schenk, Kurt; Scopelliti, Rosario; Luo, Jingshan; Wong, Lydia H.; Grätzel, Michael; Nazeeruddin, Mohammad Khaja
<x xml:space="preserve">Abstract</x> Spiro is beautiful. Two spiro-type molecules are compared at molecular level via single-crystallography. Through molecular engineering, we synthesized new hole transporting material PST1 which works efficiently in perovskite solar cells without cobalt dopant.